Flame retardant phase change thermal insulation material and preparation method thereof
By introducing phenylphosphonic acid and aziridine crosslinking agent into organic phase change insulation materials, the flame-retardant phase change insulation materials are formed, which solves the flammability problem and achieves efficient application in construction and other fields. Improves the mechanical properties and environmental friendliness of the material.
Patent Information
- Application Number
- CN202311813040.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-27
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2043-12-27
AI Technical Summary
Organic phase change insulation materials are flammable, limiting their application in areas where there are strict requirements for flame retardant grades, especially in areas such as construction and batteries.
Using raw materials such as polyethylene glycol, phenylatic dianhydride, phenylphosphonic acid and aziridine crosslinking agent, phenylphosphonic acid is introduced as flame retardant components through chemical bonds to form phase change insulation with flame retardant effect and adjust the mechanical properties by adjusting the raw material ratio.
It has obtained materials with excellent performance in thermal insulation, thermal insulation and flame retardant, which has high application value. The phosphorus flame retardant components do not contain halogen, are environmentally friendly, have higher safety, and controllable production costs.
Smart Images

Figure CN117700704B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of phase change materials, and in particular to a flame retardant phase change thermal insulation material and a preparation method thereof. Background Art
[0002] Phase change materials will undergo phase change in a specific temperature range and absorb and release a large amount of heat during the phase change process. Since the temperature change of the material during the phase change process is not obvious, it has a wide range of application prospects in thermal insulation, such as building insulation and energy saving, automobile insulation, and food insulation and preservation. Phase change thermal insulation materials are divided into organic systems and inorganic systems. Compared with inorganic phase change thermal insulation materials, organic thermal insulation materials have many advantages such as acid and alkali resistance and corrosion resistance. The leakage problem of traditional organic phase change thermal insulation materials during use has been effectively solved, but in addition to the leakage problem, organic phase change thermal insulation materials have an obvious defect-flammability. This shortcoming limits the application of organic phase change thermal insulation materials, especially in some fields such as construction and batteries that have strict requirements on flame retardancy. Therefore, the development of flame retardant phase change materials is very necessary. Summary of the invention
[0003] The purpose of the present application is to provide a flame-retardant phase-change thermal insulation material and a preparation method thereof, wherein the product material has thermal insulation properties and a flame-retardant effect at the same time, and its efficacy can remain stable during long-term use, and it has excellent thermal insulation, flame-retardant and mechanical properties, and has extremely high application value.
[0004] The technical solution of this application is as follows:
[0005] On the one hand, the embodiment of the present application provides a flame retardant phase change thermal insulation material, which is prepared from raw materials including the following components in parts by weight:
[0006] 50-73 parts of polyethylene glycol, 1-5 parts of pyromellitic dianhydride, 7-15 parts of phenylphosphonic acid, 5-35 parts of aziridine cross-linking agent, 0-3 parts of catalyst and organic solvent.
[0007] Furthermore, in some embodiments of the present application, the catalyst is stannous octoate or dibutyltin dilaurate.
[0008] Furthermore, in some embodiments of the present application, the organic solvent is one or more of N,N-dimethylformamide, N,N-dimethylacetamide, ethyl acetate, toluene and xylene.
[0009] Furthermore, in some embodiments of the present application, the molecular weight of the polyethylene glycol is 2000-100000.
[0010] On the other hand, the present invention also provides a method for preparing a flame retardant phase change thermal insulation material, which comprises the following steps:
[0011] Preparation of the first material: melt polyethylene glycol and add pyromellitic anhydride to react, cool after the reaction is completed to obtain the first material for standby use;
[0012] Preparation of the second material: dissolving phenylphosphonic acid in an organic solvent to obtain a phenylphosphonic acid solution, mixing the phenylphosphonic acid solution with the prepared first material, and then adding an aziridine cross-linking agent to obtain the second material;
[0013] Preparation of finished material: pouring the second material into a mold for curing, and then removing the residual organic solvent to obtain the finished material.
[0014] Furthermore, in some embodiments of the present application, in the above-mentioned first material preparation step, polyethylene glycol is placed in a reaction kettle, heated to 100° C. to melt it, and then pyromellitic anhydride is added and reacted at 100±10° C. for 3 hours.
[0015] Furthermore, in some embodiments of the present application, in the above-mentioned first material preparation step, after the reaction is completed, the temperature is cooled to 40-80° C. to obtain the second material, which is kept warm for later use.
[0016] Furthermore, in some embodiments of the present application, in the second material preparation step, a catalyst is added at the same time as the aziridine cross-linking agent.
[0017] Furthermore, in some embodiments of the present application, in the above-mentioned finished material preparation step, the curing treatment is carried out at 40-80° C. for 2 h.
[0018] Compared with the prior art, the embodiments of the present application have at least the following advantages or beneficial effects:
[0019] With respect to the first aspect, the embodiment of the present application provides a flame-retardant phase-change thermal insulation material, which uses phenylphosphonic acid as a flame-retardant active ingredient and is introduced into the cross-linked network of a polyurethane material in the form of a chemical bond, thereby obtaining a phase-change thermal insulation material with a flame-retardant effect. At the same time, it uses a phosphorus-based flame-retardant component and does not contain halogen, which is more environmentally friendly and safer. Among them, the catalyst can increase the preparation reaction rate and can be selected and added according to actual needs.
[0020] In addition, pyromellitic anhydride has two functions: one is to extend the molecular chain as a chain extender, and the other is to generate carboxyl groups when reacting with polyethylene glycol, providing reaction sites for subsequent reactions; aziridine crosslinking agent provides a stable three-dimensional network structure for the material as a crosslinking agent. The crosslinking density can be adjusted by adjusting the dosage ratio of pyromellitic anhydride and aziridine crosslinking agent in the raw materials, and then the mechanical properties of the product material can be adjusted according to actual needs, thereby expanding its application range and improving the economic benefits of the product.
[0021] Regarding the second aspect, the embodiment of the present application also provides a method for preparing a flame-retardant phase-change thermal insulation material. The method has a simple process flow, involves few types of raw materials and reagents, has a simple synthesis process, and can effectively control production costs. The prepared product material has flame-retardant, thermal insulation and heat-insulating properties, and has extremely high production application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 A synthetic process roadmap of a flame retardant phase change thermal insulation material provided in this application;
[0024] Figure 2 An infrared spectrum of a flame retardant phase change thermal insulation material provided in an embodiment of the present application;
[0025] Figure 3 is the DSC curve of polyethylene glycol 4000;
[0026] Figure 4 This is a DSC curve diagram of a flame retardant phase change thermal insulation material provided in an embodiment of the present application. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0028] It should be noted that relational terms such as "first" and "second" are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the term "comprises" or any other variant thereof is intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprises..." do not exclude the existence of other identical elements in the process, method, article or device including its elements.
[0029] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application may be combined with each other.
[0030] The features and performance of the present application are further described in detail below in conjunction with the embodiments.
[0031] Example 1
[0032] The present invention provides a flame retardant phase change thermal insulation material, which is prepared by the following method:
[0033] Preparation of the first material: add 69.3 g of polyethylene glycol with a molecular weight of 4000 into a reaction kettle, heat to 100° C. to melt, then add 4.2 g of pyromellitic anhydride, react at 100° C. for 3 h, and cool to 60° C. after the reaction to obtain the first material for standby use;
[0034] Preparation of the second material: 6.9 g of phenylphosphonic acid was dissolved in a small amount of N,N-dimethylformamide to obtain a phenylphosphonic acid solution, and the phenylphosphonic acid solution was added to a reaction kettle, mixed with the prepared first material, and then 5.7 g of aziridine cross-linking agent was added, and the mixture was fully stirred to obtain the second material;
[0035] Preparation of finished material: The second material is poured into a mold, cured at 60° C. for 3 h, and then placed in a vacuum oven to remove residual organic solvent to obtain a finished material.
[0036] Example 2
[0037] The present invention provides a flame retardant phase change thermal insulation material, which is prepared by the following method:
[0038] Preparation of the first material: add 57.6 g of polyethylene glycol with a molecular weight of 4000 into a reaction kettle, heat to 100° C. to melt, then add 3.5 g of pyromellitic anhydride, react at 100° C. for 3 h, and cool to 60° C. after the reaction to obtain the first material for standby use;
[0039] Preparation of the second material: 11.5 g of phenylphosphonic acid was dissolved in a small amount of N,N-dimethylformamide to obtain a phenylphosphonic acid solution, and the phenylphosphonic acid solution was added to a reaction kettle, mixed with the prepared first material, and then 27.4 g of aziridine cross-linking agent was added, and the mixture was fully stirred to obtain the second material;
[0040] Preparation of finished material: The second material is poured into a mold, cured at 60° C. for 3 h, and then placed in a vacuum oven to remove residual organic solvent to obtain a finished material.
[0041] Example 3
[0042] The present invention provides a flame retardant phase change thermal insulation material, which is prepared by the following method:
[0043] Preparation of the first material: Add 49.7 g of polyethylene glycol with a molecular weight of 10,000 into a reaction kettle, heat to 100° C. to melt, then add 1.2 g of pyromellitic anhydride, react at 100° C. for 3 h, and cool to 60° C. after the reaction to obtain the first material for standby use;
[0044] Preparation of the second material: 14.9 g of phenylphosphonic acid was dissolved in a small amount of N,N-dimethylformamide to obtain a phenylphosphonic acid solution, and the phenylphosphonic acid solution was added to a reaction kettle, mixed with the prepared first material, and then 34.2 g of aziridine crosslinking agent and 0.1 g of dibutyltin dilaurate were added, and the mixture was fully stirred to obtain the second material;
[0045] Preparation of finished material: The second material is poured into a mold, cured at 60° C. for 3 h, and then placed in a vacuum oven to remove residual organic solvent to obtain a finished material.
[0046] Comparative Example 1
[0047] This comparative example provides a phase change material, which is mainly different from the embodiment of the present application scheme in that no phenylphosphonic acid is added, and its specific preparation method is as follows:
[0048] 87.3 g of polyethylene glycol with a molecular weight of 4000 was added to the reaction kettle, and the temperature was raised to 100°C. After the polyethylene glycol was completely melted, 5.2 g of pyromellitic anhydride was added, and the mixture was reacted at 100°C for 3 h, then cooled to 60°C, stirred evenly, and 7.5 g of aziridine crosslinking agent was added. After sufficient stirring, the mixture was poured into a mold, cured at 60°C for 3 h, and then moved into a vacuum oven to remove the residual solvent, thereby obtaining comparative sample 1.
[0049] Comparative Example 2
[0050] This comparative example provides a phase change material, which is mainly different from the embodiment of the present application scheme in that no phenylphosphonic acid is added, and its specific preparation method is as follows:
[0051] 94.2 g of polyethylene glycol with a molecular weight of 4000 was added to the reaction kettle, and the temperature was raised to 100°C. After the polyethylene glycol was completely melted, 2.3 g of pyromellitic anhydride was added, and the mixture was reacted at 100°C for 3 h, then cooled to 60°C, stirred evenly, and 3.5 g of aziridine crosslinking agent was added. After sufficient stirring, the mixture was poured into a mold, cured at 60°C for 3 h, and then moved into a vacuum oven to remove the residual solvent, thereby obtaining comparative sample 2.
[0052] Test example
[0053] The performance characterization tests were performed on the material samples provided in Examples 1 to 3 of the present application and Comparative Examples 1 to 2, respectively, as follows:
[0054] Infrared spectroscopy characterization: The samples were characterized and analyzed using a Nicoletis 50 infrared spectrometer from the American Thermofisher Company in attenuated total reflection mode. The resolution was set to 4 cm -1 , the wave number range is 400-4000 cm -1 , the test temperature is room temperature.
[0055] Differential scanning calorimetry analysis: DSC 204 F1 (Netzsch Co., Germany) was used for the test. The temperature was first raised to 120 °C at a rate of 30 °C / min and kept at this temperature for 2 min to eliminate the thermal history, then cooled to -20 °C at a rate of 10 °C / min, and then raised to 120 °C at a rate of 10 °C / min. The entire test process was carried out under N2 atmosphere.
[0056] Limiting oxygen index (LOI): The limiting oxygen index of the sample was measured using the JF-3 limiting oxygen index tester produced by Nanjing Jiangning District Analytical Instrument Factory. The sample size is 120 mm × 10 mm × 4 mm in length × width × thickness. A 50 mm scale line was marked on the sample in advance. After the sample was ignited, the timing began. If the sample burned beyond the 50 mm scale line or burned for more than 3 min, it was recorded as "excessive oxygen". If the flame extinguished before the 50 mm scale line or 3 min, it was recorded as "lack of oxygen". In this way, the gap between "excess oxygen" and "lack of oxygen" was continuously narrowed. The average value of the maximum oxygen concentration when oxygen was insufficient and the minimum oxygen concentration when oxygen was excessive was taken as the limiting oxygen index of the sample. The test standard is GB 5454-85.
[0057] Vertical combustion test (UL94): The vertical combustion test was conducted using the GZF-5 horizontal vertical combustion tester produced by Wuhan Glemo Testing Equipment Co., Ltd. The sample size was 120 mm × 13 mm × 4 mm. ASTM-3801-20 was used as the standard for judging the combustion grade. A piece of 50 mm × 50 mm absorbent cotton was placed about 300 mm directly below the sample. The sample was ignited by the Bunsen burner for 10 s and then removed. The flame burning time was recorded as t1. If the sample flame goes out within 30 s after the flame is removed, the sample should continue to be ignited for 10 s. Remove the Bunsen burner and record the second flame and flameless burning time as t2. At the same time, during the combustion of the sample, attention should be paid to whether there are molten droplets dripping and whether the molten droplets ignite the absorbent cotton below. Each sample should be tested at least 5 times.
[0058] The product material synthesis process route provided in the embodiments of this application is as follows Figure 1 shown.
[0059] The test results are shown in Table 1 and Figures 2 to 4 shown.
[0060] Table 1
[0061]
[0062] As shown in Table 1, when the addition amount of phenylphosphonic acid is 8.01%, the vertical combustion level of the material has reached the VO level, and the limiting oxygen index is 29, which is a flame retardant material. When no phenylphosphonic acid is added, the limiting oxygen index of the sample is only 22.3, which is a flammable material.
[0063] like Figure 2 As shown, it is the infrared spectrum of the product material provided in Example 1 of the present application, and its 1733 cm -1The characteristic peak at 1646 cm-1 is attributed to the stretching vibration peak of the carbonyl group on the ester bond generated by the esterification reaction of polyethylene glycol and pyromellitic dianhydride; the ring-opening cross-linking reaction of aziridine can generate secondary amines. -1 The bending vibration of NH at 1197 cm -1 There is an obvious characteristic absorption peak at the PO bond stretching vibration, indicating that phenylphosphonic acid has been successfully introduced. This proves that a flame retardant phase change thermal insulation material has been successfully obtained.
[0064] like Figure 3 As shown, it is the DSC curve of polyethylene glycol with a molecular weight of 4000.
[0065] like Figure 4 As shown, it is the DSC curve of the product material provided in Example 1 of the present application.
[0066] contrast Figure 3 and Figure 4 It can be seen that after polyethylene glycol is introduced into the flame retardant phase change thermal insulation material, its crystallization behavior and melting behavior do not change significantly, indicating that the flame retardant phase change thermal insulation material has excellent phase change performance.
[0067] In summary, the embodiments of the present application provide a flame-retardant phase-change thermal insulation material and a preparation method thereof, which uses phenylphosphonic acid as a flame-retardant active ingredient and is introduced into the cross-linked network of a polyurethane material in the form of a chemical bond, thereby obtaining a phase-change thermal insulation material with a flame-retardant effect, and at the same time, it uses a phosphorus-based flame-retardant component and does not contain halogen, which is more environmentally friendly and safer; and the cross-linking density can be adjusted by adjusting the dosage ratio of pyromellitic anhydride and aziridine cross-linking agent in the raw material, and then the mechanical properties of the product material can be adjusted according to actual needs, thereby expanding its application range and improving the economic benefits of the product. The method has a simple process flow, a small number of raw materials and reagents involved, a simple synthesis process, and can effectively control production costs; the prepared product material has the properties of flame retardancy, thermal insulation and heat insulation, and has extremely high production application value.
[0068] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
Claims
1. A flame retardant phase change thermal insulation material, characterized in that: The invention is prepared from the following raw materials by weight: 50-73 parts of polyethylene glycol, 1-5 parts of pyromellitic dianhydride, 7-15 parts of phenylphosphonic acid, 5-35 parts of aziridine cross-linking agent, 0-3 parts of catalyst and organic solvent; It is prepared by a method comprising the following steps: Preparation of the first material: melt polyethylene glycol and add pyromellitic anhydride to react, cool after the reaction is completed to obtain the first material for standby use; Preparation of the second material: dissolving phenylphosphonic acid in an organic solvent to obtain a phenylphosphonic acid solution, mixing the phenylphosphonic acid solution with the prepared first material, and then adding an aziridine cross-linking agent to obtain the second material; Preparation of finished material: pour the second material into the mold for curing, and then remove the residual organic solvent to obtain the finished material.
2. The flame retardant phase change thermal insulation material according to claim 1, characterized in that: The catalyst is stannous octoate or dibutyltin dilaurate.
3. The flame retardant phase change thermal insulation material according to claim 1, characterized in that: The organic solvent is one or more of N,N-dimethylformamide, N,N-dimethylacetamide, ethyl acetate, toluene and xylene.
4. The flame retardant phase change thermal insulation material according to claim 1, characterized in that: The molecular weight of the polyethylene glycol is 2000-100000.
5. A method for preparing the flame-retardant phase-change thermal insulation material according to any one of claims 1 to 4, characterized in that: It includes the following steps: Preparation of the first material: melt polyethylene glycol and add pyromellitic anhydride to react, cool after the reaction is completed to obtain the first material for standby use; Preparation of the second material: dissolving phenylphosphonic acid in an organic solvent to obtain a phenylphosphonic acid solution, mixing the phenylphosphonic acid solution with the prepared first material, and then adding an aziridine cross-linking agent to obtain the second material; Preparation of finished material: pour the second material into the mold for curing, and then remove the residual organic solvent to obtain the finished material.
6. The method for preparing a flame retardant phase change thermal insulation material according to claim 5, characterized in that: In the first material preparation step, polyethylene glycol is placed in a reaction kettle, heated to 100° C. to melt it, and then pyromellitic dianhydride is added and reacted at 100±10° C. for 3 h.
7. The method for preparing a flame retardant phase change thermal insulation material according to claim 5, characterized in that: In the first material preparation step, the reaction is completed and then cooled to 40-80° C. to obtain the first material, which is kept warm for later use.
8. The method for preparing a flame retardant phase change thermal insulation material according to claim 5, characterized in that: In the second material preparation step, a catalyst is added at the same time as the aziridine cross-linking agent.
9. The method for preparing a flame retardant phase change thermal insulation material according to claim 5, characterized in that: In the step of preparing the finished material, the curing treatment is carried out at 40-80° C. for 2 h.
Citation Information
Patent Citations
Composition for preparation of phosphorus-containing copolyester foam and method for preparing phosphorus-containing copolyester foam from composition
CN105694386A
Preparation method of flame-retardant polyurethane aluminum alloy composite board
CN112194774A
